Цветок камалейника: роман / Ольга Громыко - Громыко Ольга Николаевна (Магия фэнтези, 2008)
Экземпляры: ф.11 (20170911) / Инвентарный номер: 57418 / Цена: / Сис.шифр: 84(2Рос=Рус)-4 / Авт.знак: Г 87 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-445